Chemically crosslinked polyvinyl alcohol for water shut‐off and conformance control treatments during oil production: The effect of silica nanoparticles. Issue 4 (17th November 2022) - Rajabi, M. Sadegh; Moradi, Rasoul; Andrade, L. Omar
Abstract: Polyvinyl alcohol (PVA) is a synthetic commercial polymer with the inherent hydrophilicity, thermal and chemical resistance, ecofriendly, and a high anti‐fouling potential making it an attractive choice for water treatment applications, but has been less studied for oil and gas industry applications. On the other hands, nowadays nanotechnology has gained an important space within most core areas in upstream oil and gas operations. The present work, first PVA at various concentrations, was added to 5 wt% NaCl solution and then, crosslinked by formaldehyde 37% at two different concentration ratios. To compare, a nanocomposite hydrogel was fabricated in the same way with 1 wt% silica nanoparticles (NPs). Contact angle and filtration test were performed to confirm the ability of PVA hydrogel and nanocomposite hydrogel for oil and water adsorption. Following this, a rheology measurement was made to realize the gelation time of samples and their performance for water shutoff applications. Finally, an experimental flooding setup was designed to inject the fluids into carbonate plugs in order to estimate of oil and water effective permeability, and oil recovery factor (RF) before and after the PVA hydrogel and nanocomposite hydrogel injection. Both samples wettability tests showed a super‐hydrophilic state for brine droplets and neutral state for synthetic oil droplets by using nanocomposite hydrogel. The flooding tests revealed that the PVA hydrogel was clogged the plug with blocking efficiency of 32.83% for water effective permeability and 14.60% for oil effective permeability. This value was calculated to be 50.37% for water effective permeability and 31.36% for oil effective permeability in the case of nanocomposite hydrogel injection. Oil RF was also reported to be 64.58% after injecting PVA hydrogel which was higher than nanocomposite hydrogel injection with RF of 52.08%. Abstract :